Estimation of physical microhabitat suitability for Koreoleptoxis globus (Mollusca: Gastropoda) using probability distribution models - Jin-Young Kim; Jeong-Ki Min; Ye Ji Kim; Yong Su Park; Dongsoo Kong (Journal of Ecology and Environment)
Background: Koreoleptoxis globus is an endangered candidate species of snail in South Korean streams. This species primarily inhabits streams characterized by fast current velocities and coarse-particle streambed substrates. In this study, 12 types of probability distribution models, including exponential, normal, log-normal, logistic, Weibull, gamma, beta, and Gumbel, were used to quantitatively assess the physical microhabitat preferences of K. globus. The evaluation was based on data collected from 340 sampling units across 34 sites in South Korea between April 2024 and May 2024, focusing on variables such as water depth, current velocity, and streambed substrate. Results: The best-fitting probability distribution models for each physical environmental factor were identified as follows: 1) water depth, inverted log-normal distribution, 2) current velocity, beta distribution, and 3) streambed substrate, Weibull distribution. Optimal water depth preferences ranged from 31.2 cm to 53.7 cm. Current velocity preferences ranged from 57.8 cm s-1 to 88.8 cm s-1. Substrate preferences ranged from −7.4 Φm to −5.6 Φm. The mean values for these factors were water depth of 35.8 cm, current velocity of 63.0 cm s-1, and streambed substrate of −5.7 Φm. Mode values were water depth of 44.4 cm, current velocity of 75.6 cm s-1, and substrate of −6.7 Φm. Standard deviation values were water depth of 15.8 cm, current velocity of 21.4 cm s-1, and streambed substrate of 1.5 Φm. Conclusions: Overall, the beta and Weibull distribution models demonstrated a high degree of fit, likely owing to the inherent flexibility of these models. Beta distribution models were well suited for cases with negative skewness, whereas Weibull distribution models provided a better fit for cases with positive skewness. The physical habitat characteristics of K. globus were quantitatively demontrated to correspond to riffled areas. Further research is required to explore the interactions between physical environmental factors and the impact of habitat disturbance.